Lower extremity robotic exoskeleton devices for overground ambulation recovery in acquired brain injury—A review - Karunakaran, Kiran K.; Pamula, Sai D.; Bach, Caitlyn P.; Legelen, Eliana; Saleh, Soha; Nolan, Karen J. (Frontiers in Neurorobotics, 2023)
Acquired brain injury (ABI) is a leading cause of ambulation deficits in the United States every year. ABI (stroke, traumatic brain injury and cerebral palsy) results in ambulation deficits with residual gait and balance deviations persisting even after one year. Current research is focused on evaluating the effect of robotic exoskeleton devices (RD) for overground gait & balance training. In order to understand the device effectiveness on neuroplasticity, it is important to understand RD effectiveness in the context of both downstream (functional, biomechanical and physiological) and upstream (cortical) metrics. The review identifies gaps in research areas and suggests recommendations for future research. We carefully delineate between the preliminary studies & randomized clinical trials in interpretation of existing evidence. we present a comprehensive review of the clinical and pre-clinical research that evaluated therapeutic effects of RDs using various domains, diagnosis and stage of recovery.